Diagnosis of bilateral pharyngoesophageal diverticula with using swallow contrast-enhanced ultrasound: a case report - Wan, Xue; Liu, Hongyan; Liu, Juxian; Peng, Yulan (Frontiers in Oncology, 2024)
Pharyngoesophageal diverticulum (PED) is a rare disease of the esophagus that is usually asymptomatic and often found incidentally during a thyroid ultrasound examination. Due to its anatomical location close to the thyroid, it is easily misdiagnosed as a thyroid nodule, which leads to unnecessary thyroid biopsies and surgical treatment. The occurrence of a single esophageal diverticula is common, while the existence of multiple diverticula is rare. Left side diverticula are more common than right sided ones, while bilateral occurrences are rarely reported. We report an extremely rare case of bilateral pharyngeal esophageal diverticula. The patient was a 55-year-old asymptomatic man who came to our hospital after thyroid nodules were identified in another hospital. Due to the extensive clinical experience of the ultrasound physician at our facility, the patient was suspected to have bilateral esophageal diverticula, which was confirmed by using swallow contrast-enhanced ultrasound (CEUS). Consequently, unnecessary thyroid treatments were avoided in this patient. This study shows that although bilateral pharyngeal diverticula are unusual, the possibility of their existence should be considered if nodules are located posterior to the bilateral thyroid glands and have suspicious imaging characteristics.Particular attention should be given to nodules located on the right side of the thyroid, which are sometimes overlooked easily due to their very low incidence. If real-time ultrasound cannot be used in making the diagnosis, PED can be further identified using swallowing CEUS to avoid unnecessary thyroid fine needle aspiration (FNA) and surgical treatment.